Electron tunneling into surface states through an inhomogeneous barrier: asymptotically exact solution of the problem and STM theory - Khotkevych, N.V.; Kolesnichenko, Yu.A.; van Ruitenbeek, J.M. (Физика низких температур, 2013)
We have found an asymptotically exact solution of the Schrödinger equation for electrons tunneling into surface
states through an inhomogeneous barrier of large amplitude. Assuming an elliptic dispersion law for the
charge carriers the “standing wave” pattern in the conductance of the system resulting from the electron scattering
by a single defect in the vicinity of the surface is analyzed.